2019
DOI: 10.3390/ijerph17010112
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenols as a Legacy Pollutant, and Their Effects on Organ Vulnerability

Abstract: Bisphenols are widely used in the synthesis of polycarbonate plastics, epoxy resins, and thermal paper, which are used in manufacturing items of daily use. Packaged foods and drinks are the main sources of exposure to bisphenols. These chemicals affect humans and animals by disrupting the estrogen, androgen, progesterone, thyroid, and aryl hydrocarbon receptor functions. Bisphenols exert numerous harmful effects because of their interaction with receptors, reactive oxygen species (ROS) formation, lipid peroxid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 148 publications
0
20
0
1
Order By: Relevance
“…32 Develop medical interventions to reduce EDC toxicity or eliminate EDCs from the body. 33 Increased understanding that the genetically based sensitivity of some people in the population to even small amounts of exposure means that they may require increased medical surveillance to anticipate and detect preclinical disease and intervene before more serious, chronic conditions [ensue]. 34 Prediction of long-term effect of chemical exposures using genomic classifiers will facilitate assignment of treatment and development of more effective therapy.…”
Section: Medical Interventionsmentioning
confidence: 99%
“…32 Develop medical interventions to reduce EDC toxicity or eliminate EDCs from the body. 33 Increased understanding that the genetically based sensitivity of some people in the population to even small amounts of exposure means that they may require increased medical surveillance to anticipate and detect preclinical disease and intervene before more serious, chronic conditions [ensue]. 34 Prediction of long-term effect of chemical exposures using genomic classifiers will facilitate assignment of treatment and development of more effective therapy.…”
Section: Medical Interventionsmentioning
confidence: 99%
“…They can activate the reactive oxygen species (ROS) pathway and the mitogen-activated protein kinase (MAPK) signalling pathways that lead to DNA damage and cellular death. Bisphenols might also alter immune responses by the stimulation of pro-inflammatory cytokines and the inhibition of anti-inflammatory cytokines production 59 .…”
Section: Non-persistent Organic Pollutants and Lung Function Bisphenolsmentioning
confidence: 99%
“…TH1/TH2 cells [62]. It also binds to androgen and progesterone receptors, PPAR, and the aryl hydrocarbon receptor, a ligand-dependent transcription factor present in almost every tissue [63,64]. In fact, some studies have observed that BPA can stimulate cellular responses at concentrations below the levels where it is expected to bind to the classic nuclear ERs [65,66].…”
Section: Mechanismsmentioning
confidence: 99%
“…It also binds to the thyroid hormone receptor, inhibiting the transcriptional activity stimulated by triiodothyronine (T3) [64]. This endocrine-disrupting activity explains the immunomodulatory properties of BPA observed in animal and in vitro models [63,64,67,68], as in humans [69]. The immune effects observed in relation to BPA exposure include T H 1/T H 2 cell shifts, reduction in T regulatory (Treg) cells (which are important in controlling proinflammatory reactions), T H 17 alterations (T H 17 are involved in the pathogenesis of various autoimmune and inflammatory diseases), reduced innate immunity, increased B-cell count and activity, and increased oxidative stress and expression of immunity-related genes [63,64,70].…”
Section: Mechanismsmentioning
confidence: 99%